Psychological tests - "Anstey, Edgar" (London, 1966)
This book is intended both for professional test constructors and for the many people who are concerned with intelligence and other psychological tests in that they have to interpret test results or to decide whether or not tests should be used in a particular context.
Keywords: Psychology